2018
DOI: 10.1039/c7sc04706a
|View full text |Cite
|
Sign up to set email alerts
|

Inedible saccharides: a platform for CO2 capturing

Abstract: Renewable materials, viz. cellulose, chitin, chitosan and cyclodextrins are promising alternatives to petroleum-based feedstocks for CO2 sequestration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 100 publications
0
13
0
Order By: Relevance
“…Finally, we established groundwater vulnerability zoning map through bee colony optimization and finally established groundwater vulnerability zoning map through bee colony optimization (Pini et al 2010 ). It was found that the least high-risk areas were mainly distributed in plain areas, with a total area of 53.93 km 2 , accounting for 19.32% of the land area (Qaroush et al 2018 ); the highly vulnerable area is about 42.84 km 2 , accounting for 15.35%. Finally, the evaluation results of drastic system and drasli Ke system are compared and analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we established groundwater vulnerability zoning map through bee colony optimization and finally established groundwater vulnerability zoning map through bee colony optimization (Pini et al 2010 ). It was found that the least high-risk areas were mainly distributed in plain areas, with a total area of 53.93 km 2 , accounting for 19.32% of the land area (Qaroush et al 2018 ); the highly vulnerable area is about 42.84 km 2 , accounting for 15.35%. Finally, the evaluation results of drastic system and drasli Ke system are compared and analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…The sorption capacities of affiliated systems in the literature were measured using different techniques and sorption conditions, which may hinder a fair comparison among the sorbents investigated by our research group. 17,18 However, it is useful to compare systems that have been measured in the same temperature range with a similar mechanism of action ( i . e .…”
Section: Resultsmentioning
confidence: 99%
“…31 Furthermore, they can also be synthesized using green carbonylating agents such as propylene carbonate, as innovated by our research group, 32 CO 2 , 33,34 or sc CO 2 . 35 Our recent findings on bio-renewables/materials, 36–39 fine chemicals, 22,40–44 and natural/synthetic polymeric materials 45–50 serving as scaffolds for CO 2 sequestration/utilization unveil a newly developed strategy that can develop mechanistic approaches for CO 2 capture. 51,52…”
Section: Introductionmentioning
confidence: 99%